2017
DOI: 10.1186/s40463-017-0204-4
|View full text |Cite
|
Sign up to set email alerts
|

Using cone beam CT to assess the upper airway after surgery in children with sleep disordered breathing symptoms and maxillary-mandibular disproportions: A clinical pilot

Abstract: BackgroundThe surgical excision of anatomic obstructions such as adenoids, palatine or lingual tonsils are commonly performed in children with sleep disordered breathing (SDB). Imaging studies measuring airway changes post-surgery in the SDB pediatric population are scarce, rarely addresses the nasal cavity, and are based on global measures (e.g. volume) that do not represent the complexity of the upper airway anatomy. The purpose of this pilot is to test the feasibility in using cone beam CT (CBCT) to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Özer et al reliable studies have been carried out in the areas of diagnosis and treatment of upper airways and dental diseases, both in children and adults. 6,7 Although CT is a non-invasive technique, but contains ionizing radiation effects. It is important to use low-dose protocols in studies performed especially in children due to radiation exposure.…”
Section: Bjrmentioning
confidence: 99%
“…Özer et al reliable studies have been carried out in the areas of diagnosis and treatment of upper airways and dental diseases, both in children and adults. 6,7 Although CT is a non-invasive technique, but contains ionizing radiation effects. It is important to use low-dose protocols in studies performed especially in children due to radiation exposure.…”
Section: Bjrmentioning
confidence: 99%
“…This study is one of clinical pilot pertaining to the use of CBCT measurements in childhood sleep apnea 29 . A previous study by Alsufyani et al compared CBCT before and after surgery in children with sleep‐disordered breathing symptoms, and showed that the new airway measure generated by CBCT was related to changes in clinical symptoms 29 . However, overnight PSG was not applied for the evaluation of OSA in their children.…”
Section: Discussionmentioning
confidence: 99%
“…Tikku et al showed the oropharyngeal airway volume, minimal cross‐section area, and the A‐P and lateral width of the airway in OSA was significantly less than that of normal subjects 62 . However, there is a lack of such publications in the pediatric population 29 . Moreover, the CBCT studies in adults with OSA were mainly focused on oropharyngeal measurements 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a validated and objective 3D UA evaluation protocol, the effect of altered head or tongue posture on the UA volume has not been thoroughly investigated although previous studies have highlighted this association 21,25,33,34 In order to perform comparable UA studies with reliable outcomes, head posture or the cranio-cervical inclination should be in a standardized posture during image acquisition, which has been highlighted as a confounding factor in the literature 1,18,20,31,35 thus calling for this study.…”
Section: Author Manuscriptmentioning
confidence: 99%